FEMINA (WOMEN) DALAM HUKUM WARIS - Aniq, Muhammad (IAIN Pekalongan, 2013)
Abstract : In the Compilation of Islamic Law (KHI) Article 176 stated that the daughter becomes heirs with the son. The portion of the son is twice the size as of the daughter’s. Next comes the question, is it true that 2:1 of inheritance are completely against the principle of equity partnership in the Al-Qur'an? The difference share is not due to gender issues, but the difference in the duties and responsibilities imposed upon men are greater than women in the Muslim community, according to the theory of conventional standard which states: